Posted by Anonymous on Wednesday, August 7, 2013 at 1:00am.
1.
2 / ( 2 / 3 ) = ( 2 / 1 ) / ( 2 / 3 ) =
2 * 3 / ( 1 * 2 ) = 6 / 2 = 3
( 3 / 4 ) / ( 4 / 5 ) = 3 * 5 / ( 4 * 4 ) = 15 / 16
2 / ( 2 / 3 ) + ( 3 / 4 ) / ( 4 / 5 = 3 + 15 / 16 = 3 15 / 16
2.
( 2 / 3 ) / ( 5 / 6 ) = 2 * 6 / ( 3 * 5 ) = 12 / 15 = 3 * 4 / ( 3 * 5 ) = 4 / 5
2 / 5 of ( 2 / 3 ) / ( 5 / 6 ) =
( 2 / 5 ) * ( 4 / 5 ) =
2 * 4 / ( 5 * 5 ) = 8 / 25
( 8 / 25 ) / ( 3 / 10 ) = 8 * 10 / ( 3 * 25 ) =
8 * 2 * 5 / ( 3 * 5 * 5 ) =
8 * 2 / ( 3 * 5 ) =
16 / 15 = ( 15 + 1 )/ 15 =
15 / 15 + 1 / 15 = 1 1 / 15
3.
2 x < = 8 Subtract 3 to toth sides
2 x + 3 - 3 < = 11 - 3
2 x < = 8 Divide both sides by 2
2 x / 2 < = 8 / 2
x < = 4
4.
3 x + 4 > = 5 x - 8 Subtract 3 x to both sides
3 x + 4 - 3 x > = 5 x - 8 - 3 x
4 > = 2 x - 8 Add 8 to both sides
4 + 8 > = 2 x - 8 + 8
12 > = 2 x Divide both sides by 2
12 / 2 > = 2 x / 2
6 > = x
That is same x < = 6